INTIMATE FEMICIDE IN SOUTH AFRICA: COMPARING TWO STUDIES 10 YEARS APART. (7th October 2012) - Abrahams, N; Mathews, S; Jewkes, R; Martin, L; Lombard, C
Abstract : Background: The killing of a woman by an intimate partner is the most extreme outcome of intimate partner violence. Aims/Objectives/Purpose: We compare the results of a national female homicide study in South Africa that described the epidemiology of intimate femicide for 1999 with the findings from a repeat study 10 years later (2009). Methods: The methodology of the 1999 study was repeated using a retrospective design of a proportionate random sample of 38 medico-legal laboratories to identify all homicides in 2009 of women over 13 years. Data was abstracted from the mortuary file, autopsy report, and from police data. Results/Outcome: We estimated 2363 (95% CI 1702 to 3023) female homicides in 2009 compared to 3793 (95% CI 2693 to 4894) in 1999, a 47.8% lower rate (12.9/100 000 vs 24.7/100 000). Intimate femicide rates declined by 36.4% (5.6/100 000 in 2009 vs 8.8/100 000 in 1999) whereas non-intimate femicide rates declined by 49.5%. More rapes were reported among non-intimate femicides in 2009 (p=0.00) while a significant overall reduction of gun murders were found between the 2 years (p=0.04). Convictions declined among non-intimate femicides (p=0.000) (32.7% vs 23.1%) whereas it was stable for intimate femicides (37.4% vs 35.1%). Significance/Contribution to the Field: Study show homicide in South Africa is declining but gender-based homicides are disproportionately resistant to the change, and rape homicides have proportionately increased. The lesser reduction in intimate's points to poor implementation of intervention programmes for prevention of intimate partner violence.